Development of project-based modules to improve learning outcomes, critical thinking and problem-solving skills - Mindo Laura Victoria Tampubolon; Herbert Sipahutar (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
In the 21st century, students must have high knowledge and thinking skills which can be achieved through learning activities. This study aimed to develop a Project-Based Module (PBM) on the topic of determination, differentiation, and organogenesis that is feasible and effective in improving students' cognitive learning outcomes (CLO), critical thinking (CTS), and problem-solving skills (PSS). The module used the 4D developmental model consisting of define, design, develop, and disseminate, which then underwent validation and student response for its feasibility in terms of material adequacy, learning process, and layout design. The module was also tested for its effectiveness in improving CLO, CTS, and PSS. The result showed that the module was tested valid and categorized as "very worthy" as 91.6 % by material expert, learning expert, and layout expert. Students gave excellent responses to the module as 87.77 % with a very worthy category. Moreover, the independent t-test results show a significant difference in CLO (P = 0.00), CTS (P = 0.00), and PSS (P= 0.00) between the control and experimental posttest results. Thus, the project-based module improves student’s CLO, CTS, and PSS in the animal development course. Further research needs to be extended for wider-scale trials to obtain maximum results.